Dengue Virions and Antigens in Brain and Serum of Infected Mice - Brandt, Walter E. (1970)
The temporal relationships of the production of infectious dengue-2 virus and its antigens were investigated in intracerebrally infected suckling mice. Infectious virus, a slowly sedimenting noninfectious hemagglutinin (SHA), and a noninfectious soluble complement-fixing antigen (SCF) were found in the brain. Serum contained high concentrations of SCF antigen relative to infectivity when compared to SCF to infectivity ratios in the brain. Degradation of virions by Tween-80 and ether produced two antigens with sedimentation characteristics similar to the noninfectious antigens occurring naturally in infected tissues. However, the virionderived SHA differed from native SHA when examined by electron microscopy and by equilibrium centrifugation in cesium chloride. Virion-derived SCF (as well as the virions and both SHA antigens) was denatured by sodium lauryl sulfate (SLS) and 2-mercaptoethanol (2-ME), whereas native SCF retained its complement-fixing activity. SLS and 2-ME treatment of dengue-1 and dengue-2 sucrose-acetone antigens increased their serotypic specificity. The hemagglutinin present in sucrose-acetone antigens was predominantly native SHA.